A hope more powerful than the sea : one refugee's incredible story of love, loss, and survival - Fleming, Melissa (Melissa R.) (Flatiron Books, 2017)
"The story of a young Syrian refugee's attempt to reach Sweden, focusing on her ordeal in icy waters after the dilapidated fishing vessel in which she was traveling--along with 500 others--sinks"--OCLC.